2019
DOI: 10.3390/ijms20184564
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Anti-Bacterial Evaluation of Triazolyl-Pterostilbene Derivatives

Abstract: Staphylococcus aureus resistance to current antibiotics has become the greatest global challenge facing public health. The development of new antimicrobial agents is urgent and important and is needed to provide additional therapeutic options. In our previous study, we found out that pterostilbene exhibited potent antibacterial activity, especially against methicillin-resistant Staphylococcus aureus (MRSA). According to previous studies, 1,2,3-triazole, with the characteristic of increasing the interaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
4
12
0
Order By: Relevance
“…The accumulated data indicated that presence of the strong electron donating group (OMe) at ortho and para positions of phenyl ring of chalcone could enhance the antibacterial activity of the other products. In contrast, triazolyl-pterostilbene derivatives exhibited potent antibacterial activity, particularly against methicillin-resistant Staphylococcus aureus (MRSA) 126 . Among these compounds, compound 55 ( Figure 11 ) exhibited the most potent anti-MRSA activity with a minimum inhibitory concentration (MIC) value of 1.2–2.4.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The accumulated data indicated that presence of the strong electron donating group (OMe) at ortho and para positions of phenyl ring of chalcone could enhance the antibacterial activity of the other products. In contrast, triazolyl-pterostilbene derivatives exhibited potent antibacterial activity, particularly against methicillin-resistant Staphylococcus aureus (MRSA) 126 . Among these compounds, compound 55 ( Figure 11 ) exhibited the most potent anti-MRSA activity with a minimum inhibitory concentration (MIC) value of 1.2–2.4.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Consequently, bacteria develop several adaptive mechanisms to eliminate the effects of antibacterial agents, including inactivating or excluding a drug and a structure conformation modification for bypassing the drug action [23]. Notably, the global spread and the increasing populations of antibiotic-resistant microbes are global public health concerns [4,24]. More than two million people are infected by antibiotic-resistant pathogens worldwide, resulting in over 700,000 deaths each year [24].…”
Section: Discussionmentioning
confidence: 99%
“…Based on a previous study, MIC values of TGII were determined for all S. aureus strains by using the twofold broth serial dilution method [4]. Briefly, S. aureus was diluted in MH broth and cultured overnight to achieve optimal cell density of nearly 2 × 10 6 cfu/mL (OD 600 = 0.01).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound (2-(2,4-Dichlorophenyl)-3-(1H-indol-1-yl)-1-(1,2,4-1H-triazol-1-yl) propan-2-ol 1a exhibited the excellent activity against Candida, particularly against low fluconazole susceptible species. Result showed that this compound exhibited high activity as compared with fluconazole and similar to voriconazole against C. glabrata , C. krusei, and C. albicans [ 29 ].…”
Section: Main Textmentioning
confidence: 99%